2008
DOI: 10.1080/15287390802476991
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Industrial Multiwalled Carbon Nanotubes on Human Pulmonary Cells

Abstract: The aim of this study was to evaluate adverse effects of multiwalled carbon nanotubes (MWCNT), produced for industrial purposes, on the human epithelial cell line A549. MWCNT were dispersed in dipalmitoyl lecithin (DPL), a component of pulmonary surfactant, and the effects of dispersion in DPL were compared to those in two other media: ethanol (EtOH) and phosphate-buffered saline (PBS). Effects of MWCNT were also compared to those of two asbestos fibers (chrysotile and crocidolite) and carbon black (CB) nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 49 publications
5
87
1
1
Order By: Relevance
“…There have been some reports on the toxicity of CNTs using different cell types 25,26 where biological responses, such as cell viability, morphology change and DNA content, were reported to be different according to the types of cells. Recently, we found that the differences in the sensitivity to MWCNTs were caused by the volume ratio between cell and MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports on the toxicity of CNTs using different cell types 25,26 where biological responses, such as cell viability, morphology change and DNA content, were reported to be different according to the types of cells. Recently, we found that the differences in the sensitivity to MWCNTs were caused by the volume ratio between cell and MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many publications on acute or long-term consequences of industrial CNT exposures were performed in vitro by using lung cell cultures under submerged conditions (Clift et al, 2014;Snyder-Talkington et al, 2013;Tabet et al, 2009;Thurnherr et al, 2011;Wang et al, 2011). However, such exposures in suspension do not represent a realistic situation of what would be expected in the human lung when fibers are inhaled.…”
Section: Introductionmentioning
confidence: 99%
“…As stated earlier, instillation of particles implies that NP are given not as powders but as suspensions. In such preparations, NP are not present as single NP but usually as (large) agglomerates (Tabet et al 2009;Porter et al 2008;M€ oller et al 2013), which will determine how many and where the particles may deposit within the respiratory tract. Consequently, it will also have implications in the translocation of the NP, and further biological effects (Li et al 2007;Shvedova et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These suspensions depending on the dispersant will lead to the formation of agglomerates/aggregates of different number concentration, size, stability, and will behave differently from a powder of similar NP composition. These parameters can largely influence the subsequent biological effects of a given NP (Monteiro-Riviere et al 2005;Li et al 2007;Shvedova et al 2008;Tabet et al 2009;Andujar et al 2014). Andujar et al (2014).…”
Section: Introductionmentioning
confidence: 99%